The Effective Description of Strong Electroweak Symmetry Breaking - Mikulas Gintner; Josef Juran; Ivan Melo; Beata Trpisova (Communications - Scientific letters of the University of Zilina, 2010)
The actual mechanism of electroweak symmetry breaking remains the last unsolved part of the Standard model of electroweak interactions. We review the general requirements that all possible solutions must fulfill. Based on them the effective description of the mechanism can be formulated. We offer such a description which is a modified version of the so-called BESS model and discuss its properties.